Corrigendum Candidate Gene Locus for PHACE Syndrome. Am J Med Genet A. 2012;158(6):1363–1367. Doi:10.1002/ajmg.a.35341 (American Journal of Medical Genetics Part A, 2022)
The objective of this study was to characterize prenatal referrals for differences of sex development (DSD) and associated genetic diagnoses and clinical outcomes at a tertiary fetal care center. We conducted a retrospective review of prenatal referrals to our center for concern of fetal DSD. Referral indications included: sex chromosome DSD (Group 1), atypical genitalia (Group 2), and discordance between fetal chromosomal and phenotypic sex (Group 3). Maternal demographics, fetal imaging findings, genetic testing results, pregnancy outcome, postnatal genital phenotype, and endocrine evaluations were recorded. Between 2012 and 2024, 255 patients were referred: 161 for sex chromosome DSD, 85 for atypical genitalia, and 9 for fetal sex discordance. Of fetuses in Groups 2 and 3 (n = 94), cytogenetic abnormalities were identified in 15 fetuses (5 chromosome aneuploidies, 1 sex chromosome DSD, and 9 copy number variants), most with multiple congenital anomalies. Six single-gene disorders were diagnosed: two congenital adrenal hyperplasia, two androgen insensitivity syndrome, one 17-beta hydroxysteroid dehydrogenase deficiency, and one NR5A1-related testicular DSD. The overall diagnostic yield of genetic testing was 22% (21/94). Of 64 fetuses with postnatal data, 61% were 46,XY DSD, 16% were 46,XX DSD, and 22% were false positive. Cytogenetic abnormalities and single-gene disorders are implicated in prenatal presentations of DSD, some of which may have multisystemic findings or medically important interventions after birth.